Decreased Internal Phosphorus Loading From Eutrophic Sediment After Artificial Light Supplement: Preliminary Evidence From a Microcosm Experiment - Zhang, Miao; Li, Yan; Wang, Hai-Jun; Yu, Ye-Xin; Liu, Jia-Hao; Qiao, Rui-Ting; Liu, Miao; Ma, Shuo-Nan; Wang, Hong-Zhu (Frontiers in Environmental Science, 2022)
Nutrient loading reduction is an essential approach for controlling eutrophication. In addition to external nutrient loading, internal phosphorus (P) loading is usually considered one of the most important factors determining nutrient levels in water. The underwater light climate plays a pivotal role. However, few studies have been reported on the effect of light intensity on P release, and the existing studies have not drawn a definitive conclusion on whether underwater light has a positive or negative effect on P release. To confirm the effect of underwater light on internal P release, a one-month microcosm experiment was carried out (November 18-December 15, 2020) under three light intensities. The P release flux (FP) was significantly higher in the control group than in the low light group during the first two weeks (p = 0.03). No difference among treatments occurred for accumulative FP in the past four weeks, although it tended to be higher in the control than in both the low and high light groups (p > 0.05). Spearman rank correlations showed that photosynthetic photon flux density (PPFD) was positively correlated with DO, pH, Chl aPhyt and Chl aBent. DO was positively correlated with Chl aPhyt and Chl aBent. The results indicate that light may promote the growth of phytoplankton and benthic algae, both of which may increase DO and pH. DO inhibits P release from sediment and pH promotes P release from sediment. Lake-scale studies are needed to fully evaluate its effect under natural conditions, as many other factors (e.g., wind or fish disturbance) in natural lakes could regulate P release from sediments.